Aboriginal Fathers Support Groups: Bridging the Gap between Displacement and Family Balance - Manahan, Candice; Ball, Jessica (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2007)
The Aboriginal Fathers Project set out to explore the roles of fathers in British Columbia’s Aboriginal families. The project aimed to investigate the ways community programs could support fathers’ involvement with their children, and increase their participation in family-centered programs. This article brieﬂy describes the project and outlines a few of the major ﬁndings from the research. This article discusses ﬁndings from the project which highlight the impact of colonialism and assimilation processes on the roles of Aboriginal fathers. The suggestion to develop father-speciﬁc support groups and the use of traditional practices and spirituality in the support groups is discussed.